2009
DOI: 10.1016/j.jmb.2008.10.049
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin Forms Ligand-Mediated Supramolecular Complexes

Abstract: SummaryThe emergence of resistance to vancomycin and related glycopeptide antibiotics is spurring efforts to develop new antimicrobial therapeutics. High resolution structural information about antibioticligand recognition should prove valuable in the rational design of improved drugs. We have determined the X-ray crystal structure of the complex of vancomycin with N-acetyl-D-Ala-D-Ala, a mimic of the natural muramyl peptide target, and refined this structure at a resolution of 1.3 Å to R and R free values of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 57 publications
(53 reference statements)
4
45
1
Order By: Relevance
“…1e,f). Such observation is consistent with the results obtained from the size analyses of concentrated Van in aqueous solution with sizeexclusion chromatography, dynamic light scattering and smallangle X-ray scattering 35 . The formation of the nanometer-sized Van aggregates is a result of the fact that Van easily forms noncovalent, asymmetric dimmers-mostly through multiple hydrogen bondwhere the dimerization surface is on the opposite side (back) of the molecule from the ligand binding pocket 36 .…”
Section: Dependence Of Bacterium-capturing Capability On Van-coatingsupporting
confidence: 91%
See 1 more Smart Citation
“…1e,f). Such observation is consistent with the results obtained from the size analyses of concentrated Van in aqueous solution with sizeexclusion chromatography, dynamic light scattering and smallangle X-ray scattering 35 . The formation of the nanometer-sized Van aggregates is a result of the fact that Van easily forms noncovalent, asymmetric dimmers-mostly through multiple hydrogen bondwhere the dimerization surface is on the opposite side (back) of the molecule from the ligand binding pocket 36 .…”
Section: Dependence Of Bacterium-capturing Capability On Van-coatingsupporting
confidence: 91%
“…The formation of the nanometer-sized Van aggregates is a result of the fact that Van easily forms noncovalent, asymmetric dimmers-mostly through multiple hydrogen bondwhere the dimerization surface is on the opposite side (back) of the molecule from the ligand binding pocket 36 . Loll and co-workers 35 further asserted that collective back-back and side-side interactions between Van monomers facilitate the self-association formation of large supramolecular complex (more than six Van monomers). Their calculation also showed that the multiple noncovalent interactions engender variation in molecular conformation.…”
Section: Dependence Of Bacterium-capturing Capability On Van-coatingmentioning
confidence: 99%
“…Lipid II is insoluble in water and thus most investigations of the recognition of lipid II by vancomycin have involved either chemically modified or truncated fragments of lipid II [10]. NMR and X-ray crystallographic studies [11][12][13][14][15][16][17] showed that the ligand bound to the concave (front face) of vancomycin, the C-terminal carboxylic acid group of D-Ala-D-Ala interacting with the backbone amide groups of resides NLEU1, HDPY2 and ASN3. In addition, the amide group of Ala1 forms a stable hydrogen bond with the carbonyl oxygen of DPYG4.…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of ligand, the extent of the association increases by one to two orders of magnitude [23]. In addition to back-to-back dimers, crystallographic studies suggest that vancomycin also forms stable face-to-face and side-to-side interactions [12,17]. In the face-to-face dimer, the N-and C-termini of vancomycin are in close proximity, with potentially two ligand molecules sandwiched within the interface.…”
Section: Introductionmentioning
confidence: 99%
“…However, so far there is no clear understanding about the chiral recognition mechanism. Only X-ray crystallographic studies have been conducted, for example, in the case of vancomycin with the tripeptide N α , N ω -diacetyl-L-Lys-D-Ala-D-Ala [50,51] or small ligands such as N-acetyl glycine [52]. NMR Studies illustrating the interaction between solute and selector have not been published.…”
Section: Chiral Separations Mechanisms In Capillary Electrophoresismentioning
confidence: 99%